PENINGKATAN PENGETAHUAN ESTIMASI BIAYA PROYEK KONSTRUKSI BAGI SISWA SMK DI KABUPATEN BEKASI - Lenggogeni; Arief Saefudin; Zahra Aristawidya; M. Harits Diza (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2021)
Abstract Cost estimation is a field of science in building construction that demands the understanding and skills of the workforce in calculating project costs. A reliable estimator is needed in construction projects from the planning stage to the project implementation. One source of construction labor is taken from vocational high school graduates, but it turns out that the unemployment rate for SMK graduates is quite high. One of the reasons is the students' lack of insight into the implementation of construction projects, including in the area of ​​cost estimation. As an effort to increase knowledge for these SMK students, additional knowledge is provided for students of the Building Modeling and Information Design Vocational School (DPIB) in Bekasi, in the form of training on construction project cost estimation. It is hoped that the competence of DPIB Vocational School students in understanding and making estimates of construction project costs will increase so that they can meet the needs of the construction industry market, as well as in entrepreneurship in the construction sector. This activity is carried out online using the Zoom Meeting application. The number of participants was 119 students of SMKN 1 Cikarang Barat, Bekasi, who received material on Construction Project Cost Estimation. As an evaluation of the activities, pre-test and post-test were given to the participants. From the results of the pre-test and post-test, it was found that there was an increase in test score from 37 to 38, and deviation standard 15.65 to 16.73. The average number of questions answered correctly by the trainees increased by 8.26%. The obstacle that occurs is that online activities cause participants' lack of attention to listening to the material and it is difficult to control participants in the training. Abstrak Estimasi biaya merupakan suatu bidang ilmu dalam konstruksi bangunan yang menuntut pemahaman dan keterampilan tenaga kerja dalam membuat perhitungan biaya proyek. Seorang estimator yang handal sangat dibutuhkan dalam proyek konstruksi dari tahap perencanaan hingga tahap pelaksanaan proyek. Salah satu sumber tenaga kerja konstruksi diambil dari lulusan Sekolah Menengah Kejuruan, tetapi ternyata tingkat pengangguran bagi lulusan SMK cukup tinggi. Salah satu penyebabnya adalah kurangnya wawasan siswa terhadap pelaksanaan proyek konstruksi, termasuk dalam bidang estimasi biaya. Sebagai upaya meningkatkan pengetahuan bagi siswa SMK ini, maka diberikan tambahan pengetahuan bagi siswa SMK Desain Pemodelan dan Informasi Bangunan (DPIB) di Kabupaten Bekasi berupa pelatihan estimasi biaya proyek konstruksi. Melalui kegiatan ini, diharapkan kompetensi siswa SMK DPIB dalam memahami dan membuat estimasi biaya proyek konstruksi akan meningkat sehingga dapat memenuhi kebutuhan pasar industri konstruksi, maupun dalam berwirausaha di bidang konstruksi. Kegiatan ini dilaksanakan secara daring menggunakan aplikasi Zoom Meeting. Jumlah peserta adalah 119 siswa SMKN 1 Cikarang Barat, Bekasi yang menerima materi mengenai Estimasi Biaya Proyek Konstruksi Sederhana. Sebagai evaluasi kegiatan, diberikan pre-test dan post-test kepada peserta. Dari hasil pre-test dan post-test, diketahui bahwa adanya peningkatan pengetahuan dari skor 37 menjadi 38, dengan standar deviasi sebesar 15,65 menjadi 16,73. Rata-rata butir soal yang dijawab benar oleh peserta pelatihan mengalami kenaikan sebesar 8,26%. Kendala yang terjadi adalah kegiatan online menyebabkan kurangnya perhatian peserta untuk menyimak materi dan sulitnya mengendalikan peserta dalam pelatihan.